Mothers’ facilitation of the occupational engagement of their children with FASD: a qualitative descriptive study in an under-resourced district in South Africa - Coetzee, Lian-Marie (Department of Health and Rehabilitation Sciences, 2020)
South Africa has the highest reported prevalence of Fetal Alcohol Spectrum Disorder (FASD) worldwide. The high prevalence is aggravated by limited remedial and rehabilitative services in the rural Northern Cape. Parents requested guidance to facilitate the development of their children with FASD. Understanding their needs and strengths will inform intervention programmes to create the stable environments children with FASD require for optimal life outcomes. The aim of the study is to explore the way that mothers facilitate the occupational engagement of their children with FASD as well as the challenges they face. Using a qualitative descriptive study design, the author purposively selected mothers to reveal three turning points in the lives of their children. Semi structured- and photo-elicitation interviews highlighted mothers’ experiences. Interviews were transcribed verbatim and inductively analysed with content analysis. Two themes emerged, namely, “Doing together” and “Varying access to engagement”. The findings of this study highlight the important role mothers play to facilitate the occupational engagement of children with FASD. Recognising mothers as agents of change and including them in intervention will enhance occupational therapy practice in the area of FASD.